ByzRev 05.2023.019: Karin Krause, Divine Inspiration in Byzantium. Notions of Authenticity in Art and Theology.: Cambridge: Cambridge University Press, 2022 - Sprecher, Christopher (The Byzantine Review, 2023)
Karin Krause, Divine Inspiration in Byzantium. Notions of Authenticity in Art and Theology. Cambridge: Cambridge University Press, 2022. xvii + 443 pp. – ISBN 978-1-108-83099-7 (€ 112.90).